Serum insulin-like growth factor-1 and epidemiological evidence of the risk of prostate cancer - Fang, Bo; Xiao, Hui; Fang, Ze (Frontiers in Oncology, 2026)
ObjectiveTo systematically evaluate the epidemiological association between serum insulin-like growth factor-1 (IGF-I) levels and the risk of prostate cancer, in order to provide evidence-based support for risk stratification and early prevention of prostate cancer.MethodsIn accordance with the PRISMA statement, major domestic and international databases were systematically searched. Cohort studies, case-control studies, and Mendelian randomization studies reporting the relationship between serum IGF-I and prostate cancer risk were included. A random-effects model was used to combine effect estimates, assess heterogeneity, and perform subgroup analysis and meta-regression. Sensitivity analysis and publication bias tests were used to evaluate the robustness of the results, and the GRADE system was used to assess the quality of evidence.ResultsA total of 16 studies involving multiple countries were included. The combined analysis showed that higher serum IGF-I levels were associated with an increased risk of prostate cancer (OR = 1.10, 95% CI: 1.02–1.18, P = 0.0136), with moderate heterogeneity (I²=50.6%). Subgroup analysis indicated that the association was more prominent in studies published in the last decade and in nested case-control designs, but heterogeneity was higher in large-sample and multicenter studies. Meta-regression analysis did not find that mean age or IGF-I levels significantly explained the heterogeneity. Sensitivity and publication bias analyses both supported the robustness of the main conclusion, and the GRADE assessment indicated moderate quality of evidence.ConclusionHigher serum IGF-I levels are epidemiologically associated with an increased risk of prostate cancer, but the dose-response relationship is still unclear, and the correlation is susceptible to study characteristics and confounding factors. IGF-I is expected to be a potential biomarker for prostate cancer risk stratification. It is recommended that more high-quality studies be conducted in the future to verify its clinical application value.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251174259.